INDIAN CORPORATIONS AND INTEGRATED REPORTING IN THE AGE OF DIGITAL TRANSFORMATION - Kumar, Amit; Poonia, Rajesh; Singla, Sumit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Corporate Internet Reporting (CIR) has become a pivotal aspect of modern corporate governance, driven by the demand for transparency, accountability, and sustainability. This study explores the integrated reporting practices of Indian corporations, focusing on the alignment of financial and non-financial disclosures with stakeholder expectations in the digital era. The research adopts a mixed-methods approach, analyzing secondary data from leading corporations across diverse industries to identify trends, determinants, and challenges in CIR. It highlights the role of emerging technologies such as Artificial Intelligence, Blockchain, and the Internet of Things in enhancing reporting accuracy and stakeholder engagement. The findings reveal significant disparities in CIR adoption across sectors, emphasizing the need for standardized frameworks and greater technological integration. The study concludes with recommendations for improving CIR practices to foster transparency, trust, and sustainable growth in the corporate sector.